2016
DOI: 10.21773/boun.30.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Scale on e-Consumers’ Attitudes towards Ethically Questionable Online Behaviors

Abstract: The purpose of this study is to develop a valid and reliable scale to measure e-consumers' attitudes towards ethically questionable online behaviors (e-CEQOB). A scale measuring e-consumers' attitudes towards such behaviors was developed using the conventional steps of scale development of Churchill (1979). The generated items were reduced to 24 items following EFA. The psychometric properties of e-CEQOB were assessed on two independent non-student samples in Istanbul, Turkey (Sample 1, N=635, and Sample 2, N=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 151 publications
0
3
0
Order By: Relevance
“…Among all retail types, supermarkets are the most frequently visited places that experience shoplifting (RetailNZ, 2017). The act of stealing from supermarkets by customers is known as "shoplifting" (Daunt and Greer, 2015) and it is considered as an aberrant consumer behaviour (Altuna et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among all retail types, supermarkets are the most frequently visited places that experience shoplifting (RetailNZ, 2017). The act of stealing from supermarkets by customers is known as "shoplifting" (Daunt and Greer, 2015) and it is considered as an aberrant consumer behaviour (Altuna et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Freestone and Mitchell (2004) studied 24 internet-related misbehaviours, which were categorized as illegal, questionable activities, hacking related, human internet trade and downloading. Altuna et al (2016) identified and studied a number of online behaviours as ethically questionable including privacy violations, spreading misleading information and/or purchasing fake/illegal goods, lying and misconduct, propensity towards viewing/downloading/sharing violent content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following the lines of Altuna et al (2016), an attempt has been made to juxtapose the online questionable behaviours examined in this study against the various types of unethical behaviours subsumed under the consumer ethics scale in an offline context (Vitell and Muncy, 2005). Table 7 presents the highest mean scores of different online behaviours against the consumer ethics scale (Vitell and Muncy, 2005).…”
Section: Continuum Of Unethical Online Behavioursmentioning
confidence: 99%